PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMEN PRIMER - Muhammad Miftakhul Rizqi; Nurmadi Harsa Sumatra (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) and firm size on earnings management in manufacturing companies in the primary consumer goods sector listed on the Indonesia Stock Exchange for the period 2020-2024. Independent variables consist of independent commissioners, audit committee, institutional ownership, managerial ownership, and firm size, while the dependent variable is earnings management measured using the Modified Jones Model. The study employed a quantitative approach using secondary data from annual financial reports. Purposive sampling yielded 172 observations from 36 companies over five years. Multiple linear regression was applied using IBM SPSS Statistics. Results show that partially, only independent commissioners have a significant negative effect on earnings management (sig. 0.000), while managerial ownership (sig. 0.057), institutional ownership (sig. 0.226), audit committee (sig. 0.584), and firm size (sig. 0.303) show no significant effect. Simultaneously, all independent variables jointly affect earnings management (sig. 0.002). The Adjusted R Square of 0.082 indicates an explanatory power of 8.2%.